Pengaruh Lingkungan Kerja Non Fisik dengan Kepuasan Kerja sebagai Variabel Intervening terhadap Turnover Intention Karyawan PT. Andika Lintas Samudera Banjarmasin - Marezza Putri Anggreani; Irwansyah Irwansyah; Nurul Wahyuni (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
The study aims to test the influence of the work environment a physical (X) and work satisfaction (Z) againts turnover intention (Y) employees in PT.Andhika Lintas Samudra Banjarmasin.Samples taken as much as 123 employees remain chosen in a probability sampling. Collecting data using the questionnaire while data analysis using the PLS (Partial Least Square) by using the smartPLS.Test result prove work environment a physical influental significant work against satisfaction employee, satisfaction influental significant turnover intention to work and work environment a physical influential significant againts turnover intention employees.  Key words: Work environment a physical, Satisfaction work and Turnover intention.